Geographic Information Science 9th International Conference, GIScience 2016, Montreal, QC, Canada, September 27-30, 2016, Proceedings - Miller, Jennifer A.; O'Sullivan, David; Wiegand, Nancy (Information Systems and Applications, incl. Internet/Web, and HCI, 2016)
This book constitutes the refereed proceedings of the 9th International Conference on Geographic Information Science, GIScience 2016, held in Montreal, QC, Canada, in September 2016. The 21 full papers presented were carefully reviewed and selected from 63 submissions. The papers are organized in topical sections such as spatial algorithms; network analysis; spatial analysis; spatial methods; user-generated data and linked data; automated cartography and geovisualization.